Pendekatan Client Centered dalam Mengatasi Kecemasan Menghadapi Perceraian - Tri Diyah Lestari; Nurjannah Nurjannah (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2022)
This study aims to see an overview of the implementation of Islamic counseling with a client centered approach to help overcome the anxiety of women who sue their husbands for divorce to be able to maintain viability both economically and socially post-divorce through careful planning. This research was conducted on the DS of a woman who experienced domestic violence through a qualitative approach using descriptive methods. Then the data that has been obtained will be analyzed descriptively through Milles and Hubarman's inductive analysis starting from data reduction, data presentation and drawing conclusions. The conclusion of this study is that the client-centered approach is able to make individuals fully responsible for the decisions they choose so that they are able to function effectively in life.